Performance assessment of Atwima Kwanwoma Rural Bank - Musah, Godwin (2014)
A thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration